The effect of the interaction of sleep onset latency and age on ischemic stroke severity via inflammatory chemokines - Zhou, Yuyu; Han, Xiaoli; Mu, Qingshuang; Xing, Lifei; Wu, Yan; Li, Cunbao; Liu, Yanlong; Wang, Fan (Frontiers in Neurology, 2024)
Objective Prolonged sleep onset latency (PSOL) and age have been linked to ischemic stroke (IS) severity and the production of chemokines and inflammation, both of which contribute to IS development. This study aimed to explore the relationship between chemokines, inflammation, and the interplay between sleep onset latency (SOL) and age in influencing stroke severity. Methods A cohort of 281 participants with mild to moderate IS was enrolled. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS), and SOL was recorded. Serum levels of macrophage inflammatory protein-1alpha (MIP-1α), macrophage inflammatory protein-1beta (MIP-1β), monocyte chemoattractant protein-1 (MCP-1), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were measured. Results NIHSS scores of middle-aged participants with PSOL were significantly higher than those with normal sleep onset latency (NSOL) (p = 0.046). This difference was also observed when compared to both the elderly with NSOL (p = 0.022), and PSOL (p < 0.001). Among middle-aged adults with PSOL, MIP-1β exhibited a protective effect on NIHSS scores (β = −0.01, t = −2.11, p = 0.039, R2 = 0.13). MIP-1α demonstrated a protective effect on NIHSS scores in the elderly with NSOL (β = −0.03, t = −2.27, p = 0.027, R2 = 0.12). Conclusion This study reveals a hitherto undocumented association between PSOL and IS severity, along with the potential protective effects of MIP-1β in mitigating stroke severity, especially among middle-aged patients.